2021
DOI: 10.1007/s00429-021-02365-x
|View full text |Cite
|
Sign up to set email alerts
|

Coding of interceptive saccades in parietal cortex of macaque monkeys

Abstract: The oculomotor system can initiate remarkably accurate saccades towards moving targets (interceptive saccades) the processing of which is still under debate. The generation of these saccades requires the oculomotor centers to have information about the motion parameters of the target that then must be extrapolated to bridge the inherent processing delays. We investigated to what degree the information about motion of a saccade target is available in the lateral intra-parietal area (area LIP) of macaque monkeys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In other studies, LIP neurons were shown to respond to visual stimuli in their sensory “receptive field” (RF) [20] and can be tuned to features like direction of motion or binocular disparity [21, 22]; RFs are re-mapped to their expected location before an upcoming saccade and RFs are also modulated by their behavioural significance [3, 23]. Visual RFs have usually been described as co-localised with MFs and to represent information about saccade targets [19, 24]. Our results presented here show that this is one option among a range of actual spatial configurations.…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, LIP neurons were shown to respond to visual stimuli in their sensory “receptive field” (RF) [20] and can be tuned to features like direction of motion or binocular disparity [21, 22]; RFs are re-mapped to their expected location before an upcoming saccade and RFs are also modulated by their behavioural significance [3, 23]. Visual RFs have usually been described as co-localised with MFs and to represent information about saccade targets [19, 24]. Our results presented here show that this is one option among a range of actual spatial configurations.…”
Section: Introductionmentioning
confidence: 99%